PENGEMBANGAN PRODUK BUBUK BUAH MANGGA (MANGIFERA INDICA L) INSTAN - Sri Agustini; Patoni A Gafar (Balai Riset dan Standardisasi Industri Palembang, 2018)
This research was part of research on manufacturing of fruit flavored instant coffee. The research was intended to obtain mangoes powder which can be applied to small industries. Research using randomized complete design with concentration of fillers as the treatment with 3 replication. Mangoes used in this research were mangga harum manis and fillers used were sugar at a concentration of 20%, 25% and 30%. The physicochemical all treatment have water content below 4%, and total plate count below 100 cfu. While the highest ascorbic acid content was obtained from 20% sugar namely 2,250±160 ppm . The level of consumer preferences were analyzed following the procedure organoleptic test by 12 panelists including color, aroma and taste. The highest score preference level of color was produced by 20% sugar that was equal to 3.5 ± 0.67; while the higest score for aroma and taste by 25% sugar that was equal to 3.4 ± 0.51; 3.9± 0.67 respectively.